Antithymocyte globulin improves the survival of patients with myelodysplastic syndrome undergoing HLA-matched unrelated donor and haplo-identical donor transplants - Wang, Hong (Sci Rep, 2017)
Significant advances have been achieved in the outcomes of patients with myelodysplastic syndromes (MDS) after both HLA-matched sibling donor transplants (MSDT) and non-MSDT, the latter including HLA-matched unrelated donor (MUDT) and haplo-identical donor transplants (HIDT). In this retrospective study, we analyzed the data of 85 consecutive patients with MDS who received allogeneic HSCT between Dec 2007 and Apr 2014 in our center. These patients comprised 38 (44.7%) who received MSDT, 29 (34.1%) MUDT, and 18 (21.2%) HIDT. The median overall survival (OS) was 60.2 months, the probabilities of OS being 63%, 57%, and 48%, at the first, second, and fifth year, respectively. Median OS post-transplant (OSPT) was 57.2 months, the probabilities of OSPT being 58%, 55%, and 48% at the first, second, and fifth year, respectively. The survival of patients receiving non-MSDT was superior to that of MSDT, median OSPT being 84.0 months and 23.6 months, respectively (P = 0.042); the findings for OS were similar (P = 0.028). We also found that using ATG in conditioning regimens significantly improved survival after non-MSDT, with better OS and OSPT (P = 0.016 and P = 0.025). These data suggest that using ATG in conditioning regimens may improve the survival of MDS patients after non-MSDT.